Evaluation Of Silicone Sealant Cure Characteristics Using A Fabricated Parallel Plate Rheometer - Wan Mohd Amin, Wan Abdur Rahman (Universiti Sains Malaysia, 2018)
The cure characteristics of a silicone sealant are important to the consumers in the construction industry as it contains useful information to ensure the sealants will not fail during its service applications. In this study, three types of Room Temperature Vulcanization (RTV) silicone sealants were used to study its cure characteristics using a fabricated parallel plate rheometer and commercial Anton Paar rheometer. The effects of curing system, temperature, oscillation frequency, and gap height were investigated. The measurement data obtained from the fabricated parallel plate rheometer, which are electrical current and angular speed were evaluated to yield the cure characteristics curve which consists of induction, curing and over cure regions. The curve was a plot of torque versus time at a constant temperature to show the progression of a crosslinking process with time. Based on the cure characteristics analysis, softening time and tack-free time were obtained. Softening time was the time where the sealant had the good flow properties that can be best applied by any mechanical means. Meanwhile, the tack-free time was the time taken before the sealant resisted damage by any contacts. Based on the results obtained, fabricated parallel plate rheometer was able to describe the curing characteristics of the studied parameters satisfactorily. It showed that the curing characteristics analysis could provide a good platform to investigate the softening and tack-free time of the silicone sealants.